2016
DOI: 10.1016/j.dib.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of producing and curing concrete using domestic treated wastewater

Abstract: We tested the setting time of cement, slump and compressive and tensile strength of 54 triplicate cubic samples and 9 cylindrical samples of concrete with and without a Super plasticizer admixture. We produced concrete samples made with drinking water and treated domestic wastewater containing 300, 400 kg/m3 of cement before chlorination and then cured concrete samples made with drinking water and treated wastewater. Second, concrete samples made with 350 kg/m3 of cement with a Superplasticizer admixture made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…The use of drinking water for mixing concrete, as recommended in standards, gives higher strength compared to those made with wastewater [2]. This again supports the need to use potable for concrete production.…”
Section: Effect On Compressive Strengthmentioning
confidence: 56%
See 3 more Smart Citations
“…The use of drinking water for mixing concrete, as recommended in standards, gives higher strength compared to those made with wastewater [2]. This again supports the need to use potable for concrete production.…”
Section: Effect On Compressive Strengthmentioning
confidence: 56%
“…Also, Al-Ghusain and Terro [17] reported that there was an increase in the slump when different wastewater with different treatment levels were used in mixing concrete. However, Asadollahfardi et al [2] found no significant effect on slump when treated wastewater was used to make concrete. This non-consistent result in slump could be as a result of the drastic reduction of impurities in the wastewater after treatment.…”
Section: Effect On Workability (Slump)mentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire used in data collection was designed by the researchers and had three sections according to the major research issues addressed in this study. Similar methods and contributions can be seen in [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . Specifically, the data presented in the article can be helpful in policy implementation and monitoring in ICT adoption and assessing the gains accruable to ICT investments, some of the articles [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] addressed similar issues.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 64%